A Comparative Study of Key Critical Factors of Waterfront Port Development: Case Studies of the Incheon and Bangkok Ports. (1st November 2015) - Lee, Paul Tae‐Woo; Wu, Jei‐Zheng; Suthiwartnarueput, Kamonchanok; Hu, Kai‐Chieh; Rodjanapradied, Rahuth
Abstract: This study explores key critical factors of waterfront port development (WPD) by applying analytic network process (ANP) and analytic hierarchy process (AHP) to the Incheon and Bangkok ports, drawing certain implications. The major findings of this paper show that the ANP draws more stable, comprehensive, and consistent results than the AHP, and the ANP ranking results of the three cases, showed four common key critical criteria of WPD exist among the top five (i.e., accessibility under community function; connectivity under port function; maritime clustering, and transformation of the port/city interface under economic function).